Wariancja innowacyjna w normie skodyfikowanej w ostatnich stu latach rozwoju polszczyzny - Zbróg, Piotr (Polonica, 2018)
The article escribes the changes in the innovative variants which appeared in the codified norm within the last century. An example of such a variant is the form zjednują, first noted in 1937 as a balanced alternate of the form zjednywam. This type of units appeared in correctness dictionaries and they competed with the primarily neutral forms. Owing to the expansiveness of the innovative variants several levels of the strength of their influence on the doublet were distinguished. The variants, which appeared in one or two dictionaries and are not noted contemporarily (e.g. the form dworka as a variant of dworku) were the weakest. The strongest were the variants which became the only ones in the contemporary times and the former do not appear or are perceived as incorrect (e.g. the form wzwierciadle displaced the form w zwierciedle). An exceptional example in the group of innovative variants where those which were primarily noted as incorrect and in the course of the codified norm evolution obtained the status of correct forms (e.g. the form romansy, rżnąć). Sometimes they were so expansive that the former variants became recessive (e.g. powątpiewać o czymś) or are no longer noted (e.g. porznąć).